REVIEW OF OCCUPATIONAL HEALTH AND SAFETY (OHS) IMPLEMENTATION IN THE FILING ROOM OF BALARAJA REGIONAL HOSPITAL - Junata, Ilfan; Rumana, Nanda Aula; Indawati, Laela; Iqbal, Muhammad Fuad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Occupational Safety and Health (OSH) plays a pivotal role in ensuring a safe, healthy, and productive workplace even in areas like hospital archives. The archives room at Balaraja Regional General Hospital stores vital medical records and is exposed to physical, chemical, biological, and ergonomic hazards. This study explores how OSH is implemented in this environment, focusing on five key indicators: hazard recognition and risk control, ergonomic practices, routine health checks, management of facilities and infrastructure, and emergency preparedness. Using a qualitative descriptive approach with a case study method, data were gathered through observations and interviews with the hospital’s OSH team leader and six archive officers. Findings show that many safety measures are well applied, including regular cleaning to control dust, OSH training sessions, use of personal protective equipment, and annual health checks in line with regulations. However, gaps remain, such as inadequate lighting, non-ergonomic chairs, and absence of a first aid kit. In conclusion, while OSH implementation meets several standards, improvements in hazard management, facilities, and ergonomics are necessary to create a safer, more comfortable workspace that supports archivists’ efficiency and well-being.